Association of walking speed with cognitive function in Chinese older adults: A nationally representative cohort study - Liu, Jianping; Cui, Kaiwang; Chen, Qian; Li, Zhiteng; Fu, Jing; Gong, Xiangwen; Xu, Hui (Frontiers in Aging Neuroscience, 2022)
Background: Slow walking speed has been shown to predict cognitive decline in older individuals, but studies conducted among Chinese older adults are scarce. We examined the association of walking speed with cognitive functions and the trajectory of cognitive decline among Chinese adults aged 60 years and older. Methods: Data was from the China Health and Retirement Longitudinal Study (CHARLS), an ongoing nationally representative prospective cohort study. Walking speed was evaluated over a straight 2.5-meter flat course at baseline and categorized into tertiles (the lowest, middle and highest). Cognitive functions were assessed at each wave in three domains: episodic memory, mental status, and global cognition. Data were analyzed using linear mixed-effects models. Results: A total of 3954 older adults (48.6% female; mean age: 67.6 ± 5.55 years) were followed for up to 7 years. Participants with lowest walking speed have poorer episodic memory (β=-0.37; 95% CI: -0.46, -0.28), mental status (β=-0.45; 95% CI: -0.60, -0.29), and global cognition (β=-0.81; 95% CI: -1.03, -0.60) over the follow-up. Compared with the highest tertile of walking speed, the lowest walking speed was associated with a faster decline in episodic memory (β=-0.04; 95% CI: -0.07, -0.02), mental status (β=-0.04; 95% CI:-0.07, -0.01), and global cognition (β=-0.06; 95% CI: -0.11, -0.01). Conclusions: Slower walking speed is associated with subsequent risk of poorer cognitive functions and faster cognitive decline in older Chinese adults.